THE IMPACT OF EMPLOYING AI IN ANALYZING STUDENTS' PERFORMANCE WHILE LEARNING BASKETBALL - M. Mazin Abdulaaima Kadhim Alsaedi (Universitas Negeri Jakarta, 2025)
Background. Artificial Intelligence (AI) is considered one of the most prominent tools of the technological revolution in this context, as it has contributed to changing teaching methods from traditional memorization approaches to interactive practices that rely on data analysis, motion simulation, and providing accurate and immediate feedback to students. Objectives. The aim of this study is to examine how using AI (AI) technologies affects the way physical education students perform when learning basketball skills. Method. A random sample of 60 students from Maysan University's physical education department (30 experimental groups trained and analyzed using an AI system based on posture tracking and motor discrimination, and 30 control groups using conventional methods) was used in this quasi-experimental study. Along with measures of learning motivation and pleasure, skill performance data (shooting from a standstill and while moving, ball handling, passing, and individual defense) were gathered both before and after. Results. The significant values (p ≤ 0.05) confirm the existence of meaningful differences in favor of the post-test, indicating the effectiveness of AI in performance improvement. Conclusion. According to the findings, the experimental group outperformed the control group in the majority of performance metrics, tactical awareness, and artificial intelligence. AI techniques (such as motion analysis via video and real-time feedback) contributed to improving the accuracy of skill execution.